Pengaruh motivasi berwirausaha, pembelajaran kewirausahaan, dan penggunaan media sosial terhadap minat berwirausaha pada mahasiswa prodi S1 pendidikan ekonomi angkatan 2017 Universitas Negeri Malang - Rosalia Vernanda; Lisa Rokhmani (Universitas Negeri Malang, 2021)
Abstract This research was conducted to determine the partial or simultaneous influence of entrepreneurship motivation, entrepreneurship learning and the using of social media on entrepreneurship interest of Economics Education departement students class of 2017, State University of Malang. The research method in this research is quantitative with the type of explanatory research. The population in this study were undergraduate students of Economics Education class of 2017 State University of Malang, with a total sample of 100 students. The sampling technique used purposive sampling and primary data collection using a questionnaire. The analysis prerequisite tests in this study include normality, multicollinearity and heteroscedasticity. The data analysis technique in this study used multiple linear regression analysis techniques. The results of the study show (1) partially there is an effect of entrepreneurship motivation on entrepreneurship interest, (2) partially there is an influence of entrepreneurship learning on entrepreneurship interest, (3) partially there is an effect of using social media on entrepreneurship interest, and (4) simultaneously there is an influence of entrepreneurship motivation, entrepreneurship learning and the using of social media on entrepreneurship interest. The conclusion of this study is that there is an influence of entrepreneurship motivation, entrepreneurship learning and the using of social media on entrepreneurship interest of Economics Education departement student at Malang State University class of 2017. Abstrak Penelitian ini bertujuan untuk menentukan pengaruh parsial atau simultan dari motivasi kewirausahaan, pendidikan kewirausahaan dan penggunaan media sosial pada minat berwirausaha mahasiswa jurusan pendidikan ekonomi, Universitas Negeri Malang, tahun 2017. Penelitian ini merupakan penilitian kuantitatif dengan tipe penelitian eksplanatori. Sampel dari penelitian ini merupakan 100 mahasiswa jurusan pendidikan ekonomi, Universitas Negeri Malang, tahun 2017. Sampel dipilih menggunakan teknik purposive sampling dan data didapatkan melalui kuesioner. Tes statistic prasyarat pada penelitian ini meliputi tes normalitas, multikolinearitas, dan heteroskedastisitas. Teknik regresi linear berganda digunakan untuk proses analisa data. Hasil analisis menunjukkan bahwa (1) adanya efek partial dari motivasi kewirausahaan pada minat berwirausaha, (2) adanya efek partial dari pendidikan kewirausahaan pada minat berwirausaha, (3) adanya efek partial dari penggunaan media sosial pada minat berwirausaha, dan (4) adanya efek simultan dari motivasi berwirausaha, pendidikan kewirausahaan, dan penggunaan media sosial pada minat berwirausaha. Sehingga, motivasi kewirausahaan, pendidikan kewirausahaan, dan penggunaan media sosial membawa pengaruh pada minat berwirausaha mahasiswa pendidikan ekonomi tahun 2017, Universitas Negeri Malang.